The Effect of Music Therapy on Joint Attention, Sensory Processing, and Social-Communication Skills in Autistic Children - Farzaneh Kiyanpoor; Akram Dehghani (مجله علوم پزشکی صدرا)
Introduction: Children with high-functioning autism spectrum disorder (ASD) primarily struggle with deficits in social-communication skills, which are further exacerbated by impairments in joint attention and sensory processing. This study aimed to investigate the effect of music therapy on joint attention, sensory processing, and social-communication skills in children with autism.Methods: This quasi-experimental study employed a pretest-posttest design with a control group and a follow-up phase. The study population included all children diagnosed with high-functioning ASD and their mothers, all of whom received services at the Zainab Center in Isfahan (Iran) during 2022-2023. A convenience sampling method was used to select 30 child-mother dyads, who were then assigned to either the experimental or control group. Baseline assessments included the Early Social-Communication Scales (ESCS), administered by the researchers, and the Winnie Dunn Sensory Profile (SP) and Autism Social Skills Profile (ASSP), completed by the mothers. The experimental group underwent 12 sessions of music therapy, while the control group remained on a waitlist. Post-intervention assessments were conducted immediately after the sessions and again after a 45-day follow-up period. Data were analyzed using repeated-measures analysis of variance (ANOVA) in SPSS software (version 24).Results: The results indicated that music therapy significantly improved joint attention (E=0.831), sensory processing (E=0.177), and social-communicative skills (E=0.265) compared to the control group (P<0.05). Both within-group and between-group effects of the intervention were statistically significant (P≤0.05), confirming the efficacy of music therapy in enhancing these domains.Conclusion: Music therapy can be effectively utilized to improve joint attention, sensory processing, and social-communication skills in children with autism.